Transfer of communications knowledge: Literacy of media conglomeration in high school students - Dionisius Lesmana; Rustono Farady Marta (University of Merdeka Malang, 2022)
Information and communication technology innovations encourage mass media business by giant media ruler groups present the phenomenon of media conglomeration with various opportunities and impacts. The objective of this community service, organized by Bunda Mulia University in collaboration with Tarakanita 2 High School, through the implementation of a media study class entitled “Media Conglomerate” for 18 students in grades 10, 11, and 12 from across the majors to show the media conglomeration phenomenon and introducing media conglomerates in Indonesia. Activities were held online through Google Meet using interaction, case studies method, and sharing video material presentations to strengthen participants’ understanding of related topics. The participants stated that this activity was profoundly educative, objective, accountable, and transparent so that the material presented was able to increase knowledge and prepare their social skills in the mass communication industry. Media literacy skills are needed, especially for high school students, as the nation’s future generation to be able to see, accept, and understand the content of mass media products wisely. Participants can sort out news objectively because they understand the subjectivity of the mass media, so they are not easily influenced and ensure that the information received is to avoid provocation, conflict, and misinformation.